2018
DOI: 10.1021/jacs.8b01017
|View full text |Cite
|
Sign up to set email alerts
|

Supported Au Nanoparticles with N-Heterocyclic Carbene Ligands as Active and Stable Heterogeneous Catalysts for Lactonization

Abstract: Attachment of N-heterocyclic carbenes (NHCs) on the surface of metal nanoparticle (NP) catalysts permits fine-tuning of catalytic activity and product selectivity. Yet, NHC-coated Au NPs have been seldom used in catalysis beyond hydrogenation chemistry. One challenge in this field has been to develop a platform that permits arbitrary ligand modification without having to compromise NP stability toward aggregation or leaching. Herein, we exploit the strategy of supported dendrimer-encapsulated metal clusters (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
92
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(95 citation statements)
references
References 57 publications
2
92
0
1
Order By: Relevance
“…The application of other chiral building blocks has recently been reported by the Toste group (Scheme 5) [74]. Besides chiral amines, amino alcohols 29 were also utilized in the synthesis of C 2 -symmetric gold(I) complexes 34.…”
Section: Cyclic C 2 -Symmetric Gold(i) Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of other chiral building blocks has recently been reported by the Toste group (Scheme 5) [74]. Besides chiral amines, amino alcohols 29 were also utilized in the synthesis of C 2 -symmetric gold(I) complexes 34.…”
Section: Cyclic C 2 -Symmetric Gold(i) Complexesmentioning
confidence: 99%
“…The respective precursors were further converted to gold(I) complexes by Nolan's procedure [58] to give products moderate to good yield. Catalysts 2019, 9, A straightforward approach to imidazolium salts 112 and gold(I) complexes 113 has recently been developed by Toste (Scheme 17) [74]. Implementing Baslé and Mauduit's protocol [39,75], the authors have prepared a series of C1-symmetric NHC precursors via an elegant one-pot protocol, directly from chiral β-amino alcohols 29, mesityl amine (110), glyoxal (30), and paraformaldehyde (31).…”
Section: Scheme 10mentioning
confidence: 99%
“…15 This is in no small part due to the inert nature and biocompatibility of gold, 16 which allows for generating different structures with a wide range of properties according to the "construction block". [17][18][19] DNA-AuNPs systems have received a large boost over the past few years, and the number of publications on this topic has grown exponentially. 20 This marked interest has been principally due to the versatile interactions between AuNPs and thiolated oligonucleotides, which allow for the easy and selective functionalization of these colloids.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that NHC ligands have the ability to enhance nanocrystal catalyst stability and increase nanocrystal catalyst activity and/or selectivity. [9][10][11][12] NHC-stabilized nanocrystals have been shown to display catalytic activity toward, for example, hydrogenations and semihydrogenations, 9,[12][13][14] lactonization, 10 asymmetric arylations, 15 Buchwald-Hartwig aminations, 16 and cross-coupling reactions. 15 NHC-stabilized nanocrystals have also been shown to be competent electrocatalysts for CO2 reduction.…”
Section: Introductionmentioning
confidence: 99%
“…17 Despite the proven benefits of applying NHC ligands to nanocrystal catalysts, they have thus far only been supported on metal nanocrystal catalysts (e.g., Ru, Au, Pt, Pd, Cu). [9][10][11][12][13][14][15][16][17][18] Therefore, the potential utility of NHC ligands as supporting ligands for other types of nanocrystal catalysts is currently unknown. Certain metal phosphide nanocrystals have emerged as an important class of catalysts for reactions such as hydrodesulfurization, [19][20][21] hydrodeoxygenation, 22 and the hydrogen evolution reaction (HER).…”
Section: Introductionmentioning
confidence: 99%